Unsaturated Fatty Acids Increase the Expression of Hepassocin through a Signal Transducer and Activator of Transcription 3‐Dependent Pathway in HepG2 Cells - Cheng, Kai‐Pi; Ou, Horng‐Yih; Hung, Hao‐Chang; Li, Chung‐Hao; Fan, Kang‐Chih; Wu, Jin‐Shang; Wu, Hung‐Tsung; Chang, Chih‐Jen (Lipids, 2018)
Hepassocin (HPS) is a hepatokine that regulates hepatocyte proliferation. It is known that HPS plays an important role in the development of nonalcoholic fatty liver diseases (NAFLD). Fatty acids, such as oleic acid (OLA), exhibit the ability to activate the signal transducer and activator of transcription‐3 (STAT3), and the binding site of STAT3 is found in the promoter region of HPS. However, the regulation of HPS by fatty acids is still obscure. To clarify the regulation of HPS, we detected the expression of HPS by western blots. In addition, a hepatic steatosis cell culture model was established by treatment of different fatty acids, including linoleic acid (LNA), oleic acid, palmitic acid, and stearic acid. The intracellular lipid accumulation was confirmed by oil red O staining. Blocking of STAT3 activity was achieved by the pretreatment of the STAT3 inhibitor, stattic. We found that activation of STAT3 by interleukin‐6 (IL‐6) was mediated in the regulation of HPS expression. Treatment of unsaturated fatty acids significantly induced intracellular lipid accumulation in HepG2 cells. Moreover, the expressions of HPS were increased in unsaturated fatty acid‐treated HepG2 cells, as compared with saturated fatty acid‐treated groups. Also, the expression of HPS induced by OLA was blocked by the inhibition of STAT3 activity. Furthermore, we found that deletion of HPS by small interfering ribonucleic acid transfection decreased the protective effect of OLA on cell viability. Taken together, we provided evidence that STAT3 plays an important role in the regulation of OLA‐induced HPS expression and the increased HPS may further participate in the development of NAFLD. In addition, the increase of HPS might be involved in the protective effect of OLA on cell viability.